2015
DOI: 10.1038/tpj.2015.24
|View full text |Cite
|
Sign up to set email alerts
|

A non-synonymous polymorphism in galectin-3 lectin domain is associated with allergic reactions to beta-lactam antibiotics

Abstract: Genetic predictors of beta-lactam (BL) allergy are mostly related to Immunoglobulin E (IgE) synthesis and atopy. Despite this context, little attention has been devoted to genes of IgE/FcɛRI pathway, such as galectin-3, a β-galactoside-binding lectin, which binds to IgE. We evaluated the association of LGALS3 polymorphisms with BL allergy in 395 Spanish and 198 Italian cases, compared with 310- and 339-matched controls, respectively. The rs11125 predicted BL allergy with an odds ratio of 4.0 in Spanish populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…Four studies replicated the discovery study in a distinct population (27)(28)(29)(30). Two studies showed the involvement of the MS4A2 gene (membrane-spanning four domains, subfamily A, member 2) (13,26).…”
Section: Genetic Predictors Of Ige-dependent Reactions To Beta-lactamsupporting
confidence: 54%
See 2 more Smart Citations
“…Four studies replicated the discovery study in a distinct population (27)(28)(29)(30). Two studies showed the involvement of the MS4A2 gene (membrane-spanning four domains, subfamily A, member 2) (13,26).…”
Section: Genetic Predictors Of Ige-dependent Reactions To Beta-lactamsupporting
confidence: 54%
“…Among 19 studies evaluating the potential genetic predictors associated with AR to BLs (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), only one study used a GWAS approach (29). Four studies replicated the discovery study in a distinct population (27)(28)(29)(30).…”
Section: Genetic Predictors Of Ige-dependent Reactions To Beta-lactammentioning
confidence: 67%
See 1 more Smart Citation
“…We also recently reported that immediate allergic reactions to BLs were associated with the rs11125 variant in the gene coding for the β-galactoside-binding lectin galectin-3, LGALS3, in 2 independent populations from Spain and Italy [14]. This secretory protein binds to IgE and FcεRI on the cell membrane of B lymphocytes and mast cells and has a role in mediator release from IgE-sensitized mast cells and basophils and also in T-cell function [14].…”
Section: Immediate Reactions To Bl Antibioticsmentioning
confidence: 99%
“…This secretory protein binds to IgE and FcεRI on the cell membrane of B lymphocytes and mast cells and has a role in mediator release from IgE-sensitized mast cells and basophils and also in T-cell function [14].…”
Section: Immediate Reactions To Bl Antibioticsmentioning
confidence: 99%